2007
DOI: 10.24266/0738-2898-25.3.117
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Excessive Overhead Irrigation on Runoff during Container Production of Sweet Viburnum

Abstract: The effects of irrigation rate on volume and nutrient content of runoff were investigated. Runoff (leachate plus un-intercepted irrigation and rain) was collected weekly for 20 weeks during production of trade #1 (2.7-liter) sweet viburnum [Viburnum odoratissimum (L.) Ker-Gawl.] fertilized with a resin-coated, controlled-release fertilizer [Osmocote 18N–2.6P–10K (18–6–12), 8–9 month 21C (70F)]. Treatments were a factorial arrangement of two irrigation rates [1 (IRR1) or 2 (IRR2) cm/day (0.39 or 0.79 in)] and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…Container nurseries have been estimated to consume upwards of 178 m 3 of water per hectare per day during peak growing season [3]. This excess of applied water leads to increased runoff or leaching of applied agrichemicals such as mineral nutrients [4] and pesticides [5]. In the near future, more Agronomy 2021, 11, 1454 2 of 15 efficient practices will need to be developed to ensure a sustainable future for and the long-term success of the container nursery industry.…”
Section: Introductionmentioning
confidence: 99%
“…Container nurseries have been estimated to consume upwards of 178 m 3 of water per hectare per day during peak growing season [3]. This excess of applied water leads to increased runoff or leaching of applied agrichemicals such as mineral nutrients [4] and pesticides [5]. In the near future, more Agronomy 2021, 11, 1454 2 of 15 efficient practices will need to be developed to ensure a sustainable future for and the long-term success of the container nursery industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, typical overhead irrigation systems for container production have relatively low irrigation efficiency (volume of water retained in substrate O volume of water applied). Water is frequently lost through spaces between pots and/or leaching from substrates, and leachate volumes increase with excessive irrigation (Bilderback, 2002;Million et al, 2007). In addition, irrigation leachate contains fertilizer and chemicals and may cause nonpoint source pollution in the environment.…”
mentioning
confidence: 99%
“…This strategy can lead to leaching and runoff of fertilizer and pesticides from the substrate. Majsztrik et al (2011) and Million et al (2007) have shown that by reducing leaching of fertilizer from container-grown ornamentals, nurseries can reduce production costs and increase profits. Previous research has also shown that efficient irrigation systems and proper scheduling can save significant amounts of irrigation water without adversely affecting crop yield or quality in ornamental production (Bacci et al, 2008;Beeson, 2012;Fereres et al, 2003).…”
mentioning
confidence: 99%